Försvinnandets kultur och mumifieringen av världen: Om tidsångest och bevarandestrategier - Smeds, Kerstin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2007)
The focus in this article is on our battling against Time, perishness and death with the aid of preservation, conservation and musealizing our material and immaterial world. A battle which, in the end, is doomed to fail, since "All that is Solid Melts into Air", sooner or later. Criticism against the ever increasing "Archive Fever" (Derrida) and obsession with History and the Past can be traced back to Quatremère de Quincy in the 1820s, and will continue through thinkers and sociologists such as Friedrich Nietzsche, Theodor W. Adorno, Jaques Derrida, Pierre Nora, Alexander Kluge, Douglas Crimp and many others. Is Europe in a state of decline, musealizing itself? So what are the options for creativity in building a future? And what should the museums do, when leaving behind the epoch — the industrial society — which gave them birth? Museums should make some adjustments to their attitude to the concept of "eternal preservation".